THE FIRST RECORDS OF MITES OF THE GENUS NEHARPYRHYNCHUS (ACARIFORMES: HARPIRHYNCHIDAE) FROM BIRDS IN PERU - Literák, Ivan (2012)
Two mite species of the genus Neharpyrhynchus (Acariformes: Harpirhynchidae) were recorded on wild birds in Peru: Neharpyrhynchus trochilinus from Amazilia lacteal, and A. chionogaster (both Apodiformes: Trochilidae) and Neharpyrhynchus tangara from Thraupis episcopus (Passeriformers: Thraupidae). Records from A. chionogaster and T. episcopus represent new hostparasite associations. Mites of this genus were found in Peru for the first time.